Do Equity Preferences Matter in Climate Negotiations? An Experimental Investigation - Astrid Dannenberg; Bodo Sturm; Carsten Vogt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper investigates in how far equity preferences may matter for climate negotiations. For this purposes we conducted a simple experiment with people who have been involved in international climate policy. The experiment, which was run via the Internet, consisted of two simple non-strategic games suited to measure the parameters of inequity aversion in a Fehr and Schmidt (1999) utility function. We find that our participants show aversion against advantageous as well as disadvantageous inequity to a considerable amount. Moreover, the degree of inequity aversion is higher compared to that of students in the similar study of Dannenberg et al. (2007). Regarding the geographical variety in our sample, we cannot confirm significant differences in the degree of inequity aversion between different regions in the world, which is in line with previous findings from the experimental literature. This finding lends support to the hypothesis that equity preferences are "hard-wired" and not much influenced by socio-economic or cultural circumstances.
Keywords: H41; C92; C91; 330; individual preferences; inequity aversion; climate policy; experimental economics; public goods; Klimaschutz; Verhandlungen; Gerechtigkeit; Präferenztheorie; Experiment; Welt